Guidelines from the 2017 European Conference on Infections in Leukaemia for management of HHV-6 infection in patients with hematologic malignancies and after hematopoietic stem cell transplantation - Ward, Katherine N; Hill, Joshua A; Hubacek, Petr; de la Camara, Rafael; Crocchiolo, Roberto; Einsele, Hermann; Navarro, David; Robin, Christine; Cordonnier, Catherine; Ljungman, Per (Haematologica, 2019)
Of the two human herpesvirus 6 (HHV-6) species, human herpesvirus 6B (HHV-6B) encephalitis is an important cause of morbidity and mortality after allogeneic hematopoietic stem cell transplant. Guidelines for the management of HHV-6 infections in patients with hematologic malignancies or post-transplant were prepared a decade ago but there have been no other guidelines since then despite significant advances in the understanding of HHV-6 encephalitis, its therapy, and other aspects of HHV-6 disease in this patient population. Revised guidelines prepared at the 2017 European Conference on Infections in Leukaemia covering diagnosis, preventative strategies and management of HHV-6 disease are now presented.
Keywords: Antiviral Agents; Europe; kombinovaná terapie; Roseolovirus Infections; antivirové látky; výsledek terapie; virová transformace buněk; lidský herpesvirus 6; lidé; Hematopoietic Stem Cell Transplantation; transplantace hematopoetických kmenových buněk; Evropa; Treatment Outcome; Immunocompromised Host; infekce roseoloviry; směrnice pro lékařskou praxi jako téma; hematologické nádory; Combined Modality Therapy; Hematologic Neoplasms; Practice Guidelines as Topic; Cell Transformation, Viral; nemoc štěpu proti hostiteli; Herpesvirus 6, Human; imunokompromitovaný pacient; Graft vs Host Disease; Humans